2013
DOI: 10.1136/acupmed-2012-010257
|View full text |Cite
|
Sign up to set email alerts
|

Use of Acupuncture for Pain Management in An Academic Korean Medicine Hospital: A Retrospective Review of Electronic Medical Records

Abstract: Objective This study aimed to identify the descriptive characteristics of patients with pain conditions who visited an academic medical centre for traditional Korean medicine (TKM). Methods This work was a retrospective review of the electronic medical records of patients who received at least one session of acupuncture for pain management from March 2010 to February 2012 in the Korean medical hospital of Pusan National University. Demographic characteristics and data on patient conditions, treatment intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
4
15
0
1
Order By: Relevance
“…As for Korea, where a dual healthcare system (a system where both conventional medicine and Korean Medicine are legally recognized by the government) has been settled, LBP was the 7th most prevalent cause of inpatient care in conventional hospitals and 1st in Korean Medicine hospitals [5]. According to a 2012 study by a national institution in Korea that specializes in complementary alternative medicine (CAM), inpatients hospitalized for lumbar spinal disorders spent six times more total medical costs than outpatients [6]. This implies that inpatient care causes considerable socioeconomic losses.…”
Section: Introductionmentioning
confidence: 99%
“…As for Korea, where a dual healthcare system (a system where both conventional medicine and Korean Medicine are legally recognized by the government) has been settled, LBP was the 7th most prevalent cause of inpatient care in conventional hospitals and 1st in Korean Medicine hospitals [5]. According to a 2012 study by a national institution in Korea that specializes in complementary alternative medicine (CAM), inpatients hospitalized for lumbar spinal disorders spent six times more total medical costs than outpatients [6]. This implies that inpatient care causes considerable socioeconomic losses.…”
Section: Introductionmentioning
confidence: 99%
“…The demographics of those seeking acupuncture and related Traditional Chinese Medicine (TCM) treatments in a variety of teaching centers has been discussed in several articles [1][2][3][4][5][6][7][8][9]. The demographics of acupuncture patients in these studies were similar.…”
Section: Introductionmentioning
confidence: 70%
“…In the US, the majority of patients were Caucasian females [1][2][3][4]. In Korean settings, the majority of patients were Asian with less of a gap between the genders [5,6]. Recognizing that TCM clinical experiences change over time and practice varies in different settings, there is a need to conduct evaluations of TCM clinic data to better inform TCM education and clinical training in the US.…”
Section: Introductionmentioning
confidence: 99%
“…Cochrane and non-Cochrane reviews have also indicated the need for further research on the effectiveness and safety of acupuncture in various contexts in these conditions 2 3 6 18. All study KMDs are acupuncture practitioners who are well experienced in treating such acute pain conditions, and they have treated musculoskeletal conditions in outpatient and inpatient settings 19. Joint discussions among the study KMDs, ED physicians and investigators revealed that current ED management of such conditions seems to be suboptimal in terms of patient satisfaction, mainly based on the clinical experiences at the hospital.…”
Section: Methods and Analysismentioning
confidence: 99%